Original article (Folia Neuropathologica, 2012)

(untitled) - Wojtera, Marcin; Sobów, Tomasz; Kłoszewska, Iwona; Liberski, Paweł P.; Brown, David R.; Sikorska, Beata
Introduction : Microglia are the resident immune cells of the CNS. They are involved in the pathogenesis of diverse neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease, prion diseases as well as multiple sclerosis, amyotrophic lateral sclerosis and AIDS dementia complex. Activated microglia up-regulate many surface receptors such as the major histocompatibility complex (MHC) or complement receptors and secrete a variety of soluble biologically active factors, which are either neurotrophic (e.g. Glia-Derived Neurotrophic Factor [GDNF]) or proinflammatory and neurotoxic (e.g. tumour necrosis factor alpha [TNF-α], interleukin 1β [IL-1β], nitric oxide [NO], superoxide, eicosanoids, quinolinic acid). Aim : The aim of this work was to assess differences in the expression of microglial markers (ferritin, CD68, and HLA-DR) between AD and Creutzfeldt-Jakob disease (CJD) brains. Material and methods Analyses were performed on 65 slices derived from 26 brains [46 CJD (20 brains), 12 AD (4 brains) and 7 controls (2 brains)]. Slices were labelled immunohistochemically using anti-ferritin, anti-HLA-DR and anti-CD68 antibodies. The nonparametric Mann-Whitney U test was used to assess quantitative differences between groups. Results : The expression of microglia markers (HLA-DR and CD68) is more noticeable in CJD than in AD or control brains. There is no difference between AD and controls. The latter statement is only true in the case of using HLA-DR or CD-68 labelling. Furthermore, ferritin is not a recommended marker in this context. Conclusions : CNS inflammation is more prominent in CJD than in AD or controls. The lack of differences between AD and controls may result from a relatively advanced neurodegeneration in AD brains. In late phases of AD, inflammation is no longer present, in contrast to the early stages of the disease.